Hubungan Perilaku Prososial (Prosocial Behavior ) Dengan Kejadian Korban Bullying Pada Remaja DI SMP Diponegoro Tumpang - Jamilatur Rohmah; Kurnia Laksana; Andi Surya Kurniawan (Jurnal Keperawatan Muhammadiyah, 2026)
Bullying is widely considered a serious problem in schools in various countries, including in Indonesia. Factors that influence the emergence of bullying are emotional, referring to typical feelings and thoughts, a biological and psychological state of a series of tendencies to act, this is related to prosocial behavior. The purpose of this research is to connect prosocial behavior with the incidence of bullying victims in adolescents at Diponegoro Tumpang Junior High School. Data were taken using quantitative methods involving 88 respondents selected by proportionate stratified random sampling technique. Data were collected using prosocial behavior questionnaire sheet and bullying victims. Data analysis used the sperman rank correlation test with a value of α = 0.005. With a total of 88 respondents, almost all of them, namely 44 (50%) experienced moderate levels of prosocial behaviour and most of them, namely 42 (48%) respondents experienced moderate levels of bullying victims. The results of statistical tests showed that the value of p = 0.000 or p < 0.005 so that there is a significant relationship between prosocial behaviour and the incidence of victims of bullying in adolescents at SMP Diponegoro Tumpang. The better the prosocial behaviour, the lower the involvement as a victim of bullying. It is recommended for the school to provide deeper knowledge about prosocial behaviour in the school environment and outside of school.